Recommendation systems for software engineering: A survey from software development life cycle phase perspective - Pakdeetrakulwong, Udsanee; Wongthongtham, Pornpit (-, 2014)
Recommendation systems have the potential to support their users for filtering information and making a decision. They have become a promising research area over the past two decades in several domains. Software development field also gain benefit from the advancement of this technology. Recommendation systems specific to software engineering can facilitate their users in a wide range of activities, i.e., requirement engineering, designing, programming, and testing. In this paper, we conduct a survey of recommendation systems for software engineering focusing in particular on what they can assist users in each software development life cycle phase. From the result of survey, we identify some open research issues that are used to outline the motivation for our future work.